2018
DOI: 10.6000/1929-4247.2018.07.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eating Disorders among Female College Students of Northern Broader University, Arar, Kingdom of Saudi Arabia

Abstract: Objective: The study aimed at examining the prevalence and correlates of eating disorder among female college students of Northern Broader University, Arar city, Kingdom of Saudi Arabia. Methods:A cross sectional survey was conducted among female college students. The total sample size was 160 (66.66% of total population of college) and stratified random sampling technique was used to select female students age ranged between 18 and 23 years from faculty of medical and faculty of applied medical science. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The study as well revealed that a higher proportion offemales had a prior knowledge about BN, underlining the fact that they are more worried and concerned about their physical image, hence many of them seeks knowledge on eating disorders. This finding agrees with the previous study of Fatima, Fatima, & Anwar (2018) who established body image disturbance was the most robust factor in eating disordered behavior, including BN, hence the reason why concerns about body image may contribute to BN.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study as well revealed that a higher proportion offemales had a prior knowledge about BN, underlining the fact that they are more worried and concerned about their physical image, hence many of them seeks knowledge on eating disorders. This finding agrees with the previous study of Fatima, Fatima, & Anwar (2018) who established body image disturbance was the most robust factor in eating disordered behavior, including BN, hence the reason why concerns about body image may contribute to BN.…”
Section: Discussionsupporting
confidence: 93%
“…Kendzor et al (2009); Hales et al (2017); Solmi et al (2016)agree that many women suffering from BNtrust that smoking reduces appetite and could be a convenient way of controlling appetite and weight. Fatima, Fatima, & Anwar (2018) like (Aljomaa, (2018) established that students with low and high BMI (body mass index) were at a higher risk of disordered eating than those with BMI scores.The study concluded that body image disturbance was the most robust factor in eating disordered behavior, including BN. A similar study was carried out by Allihaibi (2015), who also reported that in Makkah Al-Mukarramah, Saudi Arabia, the underweight student had the highest eating disorders at 29%.…”
Section: Literature Review:-mentioning
confidence: 99%
“…Previous studies indicate that EDs are more prevalent in Western cultures. Additionally, EDs are far more common among women than men, re ecting cross-cultural differences in the quest for thinness for women (Allihaibi, 2015;Fatima et al, 2018;Keel & Klump, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of eating disorders (EDs) is uncommon in SA. To date, only two studies have been carried out, one in the small city of Hail (Fatima, Fatima, & Anwar, 2018) and the other in a secondary school (Alwosaifer, Alawadh, Wahab, Boubshait, & Almutairi, 2018). There are no available studies among women in general hospitals or among women in mental health (MH) facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Egypt had a 65.0% prevalence of EDs. In Saudi Arabia (Dammam), 29.4% of females had an ED, whereas this gure was 35% and 23.3% for Taif and Arar cities, respectively [13,14,15,16] 2.0 Literature Review…”
Section: Epidemiology Of Eating Disordersmentioning
confidence: 99%